The Nature of Executive Work A Case Study - Matthaei, Emilio. (Gabler, 2010)
The work situation at the topmost levels of leadership is characterized by extreme stress, critical factors include the accountability to others such as the board and shareholders, time pressure, and permanent work overload, the latter raising particularly critical questions regarding the quality of decision making. Emilio Matthaei presents igniting insights from studying senior executives of global organizations. In so doing, he gives a powerful view to what executives really do, how long they work, where they work, what media they use, and with whom they interact. Thus, this book shows what kinds of roles executives perform in today<U+0019>s large organizations.